Post-Soviet Residential Neighbourhoods in Two Second-Order Ukrainian Cities: Factors and Models of Spatial Transformation - Gnatiuk, Oleksiy; Kryvets, Olga (Geographica Pannonica, 2018)
Post-socialist urban transformation constitutes an important segment of the contemporary urban studies.In this paper we focused on transformation processes in two typical post-Soviet residential neighbourhoods,built in the period of mass construction in the second half of XX century and located inthe Ukrainian cities of Vinnytsia and Kherson. Our goals were to reveal the spatial and temporal transformationpatterns, to identify the factors of transformation, and to delineate certain transformationmechanisms and models. The assessment of morphological and functional changes of urban objectswas carried out via field observation according to a specially developed methodology with the furthercomparison of results with urban planning documents reflecting the reality in the beginning of 1990s.Our findings permitted to identify key transformation processes (deindustrialization, commercialization,revitalization, functional diversification), to list a set of factors promoting more intense transformations,and to explain mechanisms defining existing spatial pattern of transformations within thetest neighbourhoods. Private commercial activity, including rapid development of retail sector, was themain source of transformation, thus defining its partial, fragmented and somewhere controversial nature.Since the probability of further transformation in each point of the territory is determined by thealready existing pattern, the existing heterogeneities tend to enhance with a lapse of time, and thereforethe initial stages of transformation are especially important for the further development of theneighbourhood. Despite the similar starting conditions, two neighbourhoods demonstrated differentoutcomes in terms of modernization, explained by the differences in the urban spatial structure, spatialand sectorial structure of industrial zones, position (importance) of the neighbourhood in the wholecity, as well as the economic dynamics of the city. Based on detected factors and mechanisms, we proposedmodels for further transformation intended to maximize the level of modernization within the entire test neighbourhoods.
Keywords: post-socialist city; post-Soviet residential neighbourhood; spatial transformation; transformation factors; transformation models; Ukraine